1981
DOI: 10.1002/esp.3290060306
|View full text |Cite
|
Sign up to set email alerts
|

Suspended solids concentrations and river water chemistry

Abstract: In some rivers concentrations of suspended solids are influenced to a large degree by the chemistry of the river water. This is particularly true for rivers with fine sediments draining areas where soils have high percentages of exchangeable sodium and where changes in the electrolyte concentrations during hydrologic events result in an alternation between conditions favouring dispersion and those favouring flocculation. This relationship is illustrated for low flow conditions by data from a small river in Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Suspended sediment concentrations (SSCs) are highly variable but have exceeded 100 g l À1 in some dryland rivers (Beverage and Culbertson, 1964;Nordin, 1964;Gerson, 1977;Butcher and Thornes, 1978;Imeson and Verstraten, 1981;Sharma et al, 1984b;Frostick et al, 1983;Reid and Frostick, 1987;. Suspended sediment concentrations (SSCs) are highly variable but have exceeded 100 g l À1 in some dryland rivers (Beverage and Culbertson, 1964;Nordin, 1964;Gerson, 1977;Butcher and Thornes, 1978;Imeson and Verstraten, 1981;Sharma et al, 1984b;Frostick et al, 1983;Reid and Frostick, 1987;.…”
Section: Suspended Sediment Transportmentioning
confidence: 99%
“…Suspended sediment concentrations (SSCs) are highly variable but have exceeded 100 g l À1 in some dryland rivers (Beverage and Culbertson, 1964;Nordin, 1964;Gerson, 1977;Butcher and Thornes, 1978;Imeson and Verstraten, 1981;Sharma et al, 1984b;Frostick et al, 1983;Reid and Frostick, 1987;. Suspended sediment concentrations (SSCs) are highly variable but have exceeded 100 g l À1 in some dryland rivers (Beverage and Culbertson, 1964;Nordin, 1964;Gerson, 1977;Butcher and Thornes, 1978;Imeson and Verstraten, 1981;Sharma et al, 1984b;Frostick et al, 1983;Reid and Frostick, 1987;.…”
Section: Suspended Sediment Transportmentioning
confidence: 99%
“…Imeson and Verstraten (1981) have also explained that the well-documented correlation between erosion and rainfall intensity occurs not only because of rainfall energy, but also because during a rainfall event variations in the soil solution salt dilution occur, complicating (but largely enhancing) deflocculation and dispersion. The significance for sediment entrainment and erosion is clear from Figure 2.6.10, where it can be seen how that the dispersion threshold is enhanced and dispersion persists during a flash flood in Morocco.…”
Section: Runoff Generation and Sediment Entrainmentmentioning
confidence: 99%
“…It has been reported that the average concentration of suspended solids for ground water is approximately 200 mg/L and can approach 600 mg/L in some extreme cases [45,46]. Hence, our experiment was performed in the concentration range of 50-750 mg/L of silica colloid to cover the typical and extreme ranges of suspended solids.…”
Section: µM·cm/v·s) Because the Removal Of Microalgal Cells With Ionmentioning
confidence: 97%